2011
DOI: 10.1007/s10344-011-0513-2
|View full text |Cite
|
Sign up to set email alerts
|

Qualitative detection of the NSAIDs diclofenac and ibuprofen in the hair of Eurasian otters (Lutra lutra) occupying UK waterways with GC–MS

Abstract: The pervasiveness of pharmaceuticals such as nonsteroidal anti-inflammatory drugs (NSAIDs) in the aquatic ecosystem through the discharge of wastewater, and their potential to biomagnify within this ecosystem, is now recognised. Residues of diclofenac and ibuprofen are currently being detected in surface waters and aquatic organisms throughout the UK and Europe. However, the levels of these residues in fish and other aquatic organisms, particularly lower trophic level prey species, have not yet been determined… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
18
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(18 citation statements)
references
References 35 publications
0
18
0
Order By: Relevance
“…Species that come into contact with pelage orally, either when collecting it for nesting purposes, or when feeding on a carcass, may be exposed to residues of topically applied agents. Similarly, our opportunistic analysis of otter hair showed the viability of analyzing surface hair washes to identify dermal exposure and refine the information obtained regarding ongoing exposure to compounds of interest within a given environment [79].…”
Section: Applications Of Animal Pelagementioning
confidence: 92%
See 2 more Smart Citations
“…Species that come into contact with pelage orally, either when collecting it for nesting purposes, or when feeding on a carcass, may be exposed to residues of topically applied agents. Similarly, our opportunistic analysis of otter hair showed the viability of analyzing surface hair washes to identify dermal exposure and refine the information obtained regarding ongoing exposure to compounds of interest within a given environment [79].…”
Section: Applications Of Animal Pelagementioning
confidence: 92%
“…Based on their assessment of renal lesions observed, these authors have suggested that future studies investigating renal disease in otters should consider exposure to nephrotoxic agents, such as NSAIDs [78]. This recommendation was also based on a concurrent exploratory study that investigated the viability of using hair to determine exposure to diclofenac and ibuprofen in river otters [79]. In this study, hair was opportunistically collected from a subset of the dead otters (n=28) recovered for necropsy, and both NSAIDs were qualitatively detected.…”
Section: Case Study 1: Chronic Exposure Of River Otters To Nsaids In mentioning
confidence: 99%
See 1 more Smart Citation
“…Recently diclofenac has been qualitatively detected in the hair of Eurasian otters Lutra lutra indicating that wildlife is being exposed to this compound [107]. The most severe adverse effects of diclofenac though were found in three species of vultures the Indian white-rumped one (Gyps bengalensis), the Indian one (Gyps indicus), and the slender-billed one (Gyps tenuirostris) in India and Pakistan causing a population decline [108,109].…”
Section: Nonsteroidal Anti-inflammatory Drugs: the Example Of Diclofementioning
confidence: 98%
“…The term emerging pollutants refers to natural or synthetic substances found in ecosystems. Their ecotoxic impacts on the environment and humans are already known, whereas the occurrence and environmental fate are uncontrolled or unregulated 1,2 Since the late 1990s, pharmaceutical pollutants present in natural ecosystems have been seen as an emerging environmental prob- fish and fauna, the habitat and food for these animals 15 . Several studies reported on feminisation of male fish caused by a synthetic hormone 17-a-ethinyl-estradiol in their habitat 16,17 .…”
mentioning
confidence: 99%